2007
DOI: 10.1007/s11267-006-9087-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Seasonal Dynamics from Temporal Variation in Agricultural Practices in the UK Ammonia Emission Inventory

Abstract: Most ammonia (NH 3 ) emission inventories have been calculated on an annual basis and do not take into account the seasonal variability of emissions that occur as a consequence of climate and agricultural practices that change throughout the year. When used as input to atmospheric transport models to simulate concentration fields, these models therefore fail to capture seasonal variations in ammonia concentration and dry and wet deposition. In this study, seasonal NH 3 emissions from agriculture were modelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 15 publications
(15 reference statements)
3
32
0
Order By: Relevance
“…As a primary pollutant emitted from ground-level sources, NH 3 exhibits high spatial variability in concentrations Hellsten et al, 2008;Vogt et al, 2013), confirmed by NH 3 data from the NAMN (e.g. range of 0.06-8.8 µg m −3 annual mean in 2005) (Fig.…”
Section: Spatial Variability In Nh 3 and Nh + 4 Concentrations In Relsupporting
confidence: 60%
“…As a primary pollutant emitted from ground-level sources, NH 3 exhibits high spatial variability in concentrations Hellsten et al, 2008;Vogt et al, 2013), confirmed by NH 3 data from the NAMN (e.g. range of 0.06-8.8 µg m −3 annual mean in 2005) (Fig.…”
Section: Spatial Variability In Nh 3 and Nh + 4 Concentrations In Relsupporting
confidence: 60%
“…In the case of the UK and Danish ammonia networks, areas dominated by cattle and pig show peak emissions in spring, which are reproduced by models accounting for the timing of manure spreading [30,58]. However, the UK also includes substantial background areas (see the electronic supplementary material, figure S1) with a pronounced summer maximum and winter minimum of 0. , respectively).…”
mentioning
confidence: 82%
“…In areas with more intensive livestock farming, where emissions come from either cattle or from pig and poultry farming, the largest concentrations are observed in spring and autumn, corresponding to periods of manure application to land. The spring peak in March is larger than the autumn peak in September, which coincides with the main period for manure application being in spring, before the sowing of arable crops or early on in the grass-growing period (Hellsten et al, 2007). Ammonia concentrations in these areas are also larger in summer than winter, due to warmer conditions promoting volatilization.…”
Section: Concentrationsmentioning
confidence: 93%
“…In the UK, agriculture accounts for > 80 % of total NH 3 emissions and is estimated by the National Ammonia Reduction Strategy Evaluation System (NARSES) model (Webb & Misselbrook 2004;Misselbrook et al, 2015). For the agricultural NH 3 emission maps, parish statistics on livestock numbers and crop areas are combined with satellitebased land cover data to model emissions at a 1 km resolution, using the AENEID model Hellsten et al, 2007). For reasons of data confidentiality, the 1 km data need to be aggregated to produce annual agricultural NH 3 emissions maps at a 5 km by 5 km grid resolution.…”
Section: Concentrations In Relation To Estimated Emissionsmentioning
confidence: 99%